HISTOLOGICAL EFFECTS OF CITRULLUS COLOCYNTHIS SEED AQUEOUS EXTRACT ON THYROID GLAND OF ADULT ALBINO RATS - Dr. Sadia Hussain Malik; Dr. Shumaila Sohail; Dr. Haseeb Ahmed Awan; Dr. Safia Tasawar; Dr. Huma Jawad; Dr. Sadia Zeeshan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction & Objective: The thyroid is the endocrine tissue that controls the basal metabolic rate of the body, regulates the development and growth of many organs of the body. Its active hormones are thyroxine and triiodothyronine. Citrullus colocynthis, belongs to melon family of cucurbitaceae. The current study was intended at the effects of Citrullus colocynthis seed extract on thyroid gland anatomy as its seeds are extensively used for medicinal purposes but its effects on thyroid gland has never been studied before.Methodology: An experimental study was carried out with 24 albino rats, divided equally into 4 groups A, B, C and D. Group A was control and was given 1ml of distilled water by oral gavage once daily for 28 days. All other groups received Citrullus colocynthis seed aqueous extract at different doses by oral gavage once daily for 28 days. Group B received 0.5ml/kg; Group C was given 1ml/kg while Group D was given 2ml/kg. Rats were euthanized on 29th day. Thyroid tissue examined microscopically after staining with H&E and Periodic Acid Schiff for quantitative and qualitative parameters. Results were analyzed by SPSS version 21.0.Results: Citrullus colocynthis induced a statistically significant in the colloid content. On the other hand, a significant decrease was seen in epithelial height of thyroid follicular cells. No inflammation was seen at any magnification in all the groups. No significant change was seen in number of thyroid follicles.Conclusion: It is our conjecture that flavonoids present in seeds of Citrullus colocynthis might be the underlying cause for histological changes in adult albino rats suggestive of hypo-functional state of the thyroid gland.